(2R)-2-(1,3-Dioxoisoindolin-2-yl)-3-methylbutanoic acid - Abdul Rauf Raza; Aisha Saddiqa; M. Nawaz Tahir; Sadia Saddiq (Acta Crystallographica Section E, 2011)
In the title compound, C13H13NO4, the dihedral angle between the nine-membered phthalimino ring system and the carboxylic acid group is 67.15 (9)°. An intramolecular C—H...O close contact, which forms an S(6) ring, may help to establish the molecular conformation. In the crystal, molecules are linked by O—H...O hydrogen bonds, thereby forming C(7) chains propagating in [010].